2014
DOI: 10.3892/ol.2014.2806
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of invasive micropapillary carcinoma of the breast

Abstract: The aim of the present study was to evaluate the clinical and immunohistopathological findings of invasive micropapillary carcinoma (IMPC) of the breast. In total, 25 patients were included in the present study, all of whom were diagnosed with IMPC. The mammography and ultrasound scanning (US) findings were analysed retrospectively according to the American College of Radiology Breast Imaging Reporting and Data System lexicon. Surgical specimens obtained from the patients were microscopically reviewed in conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
(19 reference statements)
3
21
0
1
Order By: Relevance
“…Our study found that the rate of ER and PR positivity was 88.0% and 75.7% respectively, significantly higher than that of IDC, which was in accord with most literature . The comparable survival outcome of IMPC was usually attributed to the high rate of ER positivity .…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that the rate of ER and PR positivity was 88.0% and 75.7% respectively, significantly higher than that of IDC, which was in accord with most literature . The comparable survival outcome of IMPC was usually attributed to the high rate of ER positivity .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a significant number of metaplastic carcinoma were found to be triple negative (84%), unlike DC, NOS which were predominantly luminal B type. The findings of our study are consistent with other studies which demonstrated that triple negative characteristic was the predominant molecular subtype in metaplastic carcinoma [ 18 , 25 ]. Due to triple negative characteristic of metaplastic carcinomas, they are regarded as more aggressive type of cancers which are often less-responsive to endocrine therapy [ 24 ].…”
Section: Main Textsupporting
confidence: 93%
“…Some studies showed HER2/ neu þ rates between approximately 10% and 30%, [14][15][16]23,24 whereas others reported between approximately 50% and 80%. 34,38,41,44 Regarding the molecular classification, more cases of IMPC fall into the luminal A and luminal B subtypes than they do with IDC-NOS. 39 The features of IMPC are summarized in the Table. In addition, IMPC should be differentiated from IDC-NOS by retraction artifacts.…”
Section: Immunophenotypementioning
confidence: 99%
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%